A note on “A new method for solving fully fuzzy linear programming problems” - Saberi Najafi, H.; Edalatpanah, S.A. (Applied mathematical modelling, 2013)
This note shows that solving fully fuzzy linear programming (FFLP) model presented by Kumar et al. [A. Kumar, J. Kaur, P. Singh, A new method for solving fully fuzzy linear programming problems, Appl. Math. Model. 35 (2011) 817–823] needs some corrections to make the model well in general. A new version is provided in this note. A simple example is also presented to demonstrate the new form.